Force multiplier: US-Japan Alliance modernization and maritime Southeast Asia - Bradford, John (2022)
Formal and informal modifications to the US-Japan Alliance have expanded the value the Alliance operational structure delivers in support of US and Japanese national and combined naval activities in Southeast Asia. This article analyzes how the Alliance now serves as an increasingly powerful force multiplier which magnifies the capabilities, efficiency, and impact of the two allies' naval activities in Southeast Asia. Unlike previous studies on the role of the United States or Japan in the region, it focuses on the evolving functionality of the Alliance operational structure. The article systematically discusses how the evolving nature of the Alliance operational structure is enabling it to provide expanded support for Southeast Asian maritime security in five areas: basing, combined operations, partnerships and access, extra-regional coordination, and cooperative capacity-building. Those evaluations enable discussions of prospects for US and Japanese initiatives in Southeast Asia.